2006
DOI: 10.1007/s00003-006-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Biological Assay to Determine the Allergenic Potential of Foods

Abstract: Abbreviations: ELISA = enzyme-linked immunosorbent assay; PCR = polymerase chain reaction; SDS-PAGE = sodium dodecyl sulfatepolyacrylamide gel electrophoresis; FcεRI = high affinity receptor for IgE; RBL = rat basophilic leukemia; PBS = phosphate-buffered saline; TBS = tris-buffered saline.Abstract: Food allergies represent a risk for many people in industrialized countries. Unrecognizable allergenic proteins of foodstuffs may be present as ingredients that are not labeled or as unknown cross-contamination. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The quantitative outcome was compared and confirmed by ELISA results of the same samples. 10 Our purpose was, through novel integration of BHRA with logarithmic modelling of the area under the curve (AUC), to develop a reliable method to quantify the total amount of allergenic food proteins in circulation. This was achieved by spiking of serum with peanut and hazelnut extracts at different concentrations followed by the integrated AUC method to estimate allergen concentrations in serum.…”
Section: A Novel Methods For Quantifying Ingested Food Allergens In Human Seramentioning
confidence: 99%
“…The quantitative outcome was compared and confirmed by ELISA results of the same samples. 10 Our purpose was, through novel integration of BHRA with logarithmic modelling of the area under the curve (AUC), to develop a reliable method to quantify the total amount of allergenic food proteins in circulation. This was achieved by spiking of serum with peanut and hazelnut extracts at different concentrations followed by the integrated AUC method to estimate allergen concentrations in serum.…”
Section: A Novel Methods For Quantifying Ingested Food Allergens In Human Seramentioning
confidence: 99%
“…A critical issue with these cell lines has been the cytotoxicity of certain human sera for rat cells, requiring high dilutions and resulting in insufficient sensitisation. A complete review on recent developments in RBLs can be found in and their use in allergenicity assessment of food products in (VOGEL et al, 2006).…”
Section: Basophilsmentioning
confidence: 99%
“…The human F ce RI allowed these cells to bind IgE from sera of allergic subjects and subsequently be activated in allergen-specific manners. Mediator release by humanized RBL cells provided an appropriate cell-based assay to measure the biological activity of allergens in vitro and, over time, one that proved to be sensitive, specific, and reproducible (Blanc et al, 2009;Dibbern et al, 2003;Kaul et al, 2007;Untersmayr et al, 2005;Vogel et al, 2006). Humanized RBL cells, in combination with human serum pool, might then represent a preferred test system.…”
Section: Rat Basophil Leukemia (Rbl) Cell Modelmentioning
confidence: 99%
“…Therefore, RBL cell activation mediated through serum IgE is a result of complex relationships not only dependent on allergenspecific IgE content, but also the capacity to efficiently sensitize cells and trigger signaling responses that lead to degranulation. Further, some serum factors may hamper binding of IgE to F ce RI expressed on the cell membrane and adverse effects on the cells occur (Dibbern et al, 2003;Marchand et al, 2003;Vogel et al, 2006). Those factors and how they may act on cells to interfere with the assay have not yet been specifically identified.…”
Section: Rat Basophil Leukemia (Rbl) Cell Modelmentioning
confidence: 99%
See 1 more Smart Citation